2023
DOI: 10.1037/rev0000328
|View full text |Cite
|
Sign up to set email alerts
|

Measurement models for visual working memory—A factorial model comparison.

Abstract: Several measurement models have been proposed for data from the continuous-reproduction paradigm for studying visual working memory: The original mixture model (Zhang & Luck, 2008) and its extension (Bays, Catalao, & Husain, 2009); the interference measurement model (Oberauer, Stoneking, Wabersich, & Lin, 2017), and the target confusability competition model (Schurgin, Wixted, & Brady, 2020). This article describes a space of possible measurement models in which all existing models can be placed. The space is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
4
14
0
Order By: Relevance
“…1). Furthermore, our findings on the advantage of the von Mises over the exponential responsiveness function are consistent with recent results reported by Oberauer (2021). By combining features of different descriptive models of WM within a space of possible models and fitting them to analogue report WM data, Oberauer demonstrated that a version of a model with a von…”
Section: Recall Errorsupporting
confidence: 91%
“…1). Furthermore, our findings on the advantage of the von Mises over the exponential responsiveness function are consistent with recent results reported by Oberauer (2021). By combining features of different descriptive models of WM within a space of possible models and fitting them to analogue report WM data, Oberauer demonstrated that a version of a model with a von…”
Section: Recall Errorsupporting
confidence: 91%
“…Whereas in the first variant, the amount of noise (relative to the strength of the memory signal, as represented by Ac and Aa) is represented by the weight parameter b, in the second variant, it is represented by σ. A recent comparison of measurement models for the continuous-reproduction task (Oberauer, 2021) revealed that models using Luce's choice rule on exponentially transformed memory signals as in Equation ( 6) fit the data better than models with Luce's choice rule on untransformed signals (Equation ( 5)).…”
Section: Basic Architecturementioning
confidence: 99%
“…Additionally, the fact that the IMM assumes continuous activations underlying the retrieval of memory representations adds a third account to the explanation of capacity limits in visual working memory, that is capacity being limited by bindings (Oberauer, 2021).…”
Section: Theoretical Considerationsmentioning
confidence: 99%